Mechanically robust amino acid crystals as fiber-optic transducers and wide bandpass filters for optical communication in the near-infrared - Durga Prasad Karothu (Nature Portfolio, 2021)
Fiber-optics based on organic crystals could have potential for unique telecommunications applications but typically transmit visible wavelengths. Here the authors present mechanically robust organic crystals with favourable optical properties across the main telecommunication bands in the near-infrared.